2016
DOI: 10.1038/srep26967
|View full text |Cite
|
Sign up to set email alerts
|

Cotesia vestalis teratocytes express a diversity of genes and exhibit novel immune functions in parasitism

Abstract: Some endoparasitoid wasps lay eggs that produce cells called teratocytes. In this study, we sequenced and analyzed the transcriptome of teratocytes from the solitary endoparasitoid Cotesia vestalis (Braconidae), which parasitizes larval stage Plutella xylostella (Plutellidae). Results identified many teratocyte transcripts with potential functions in affecting host immune defenses, growth or metabolism. Characterization of teratocyte-secreted venom-like protein 8 (TSVP-8) indicated it inhibits melanization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 53 publications
0
46
0
1
Order By: Relevance
“…Solitary (Gao et al., ) and gregarious species (Vos & Vet, ) are found in the genus Cotesia , but C. icipe has consistently proven to be a solitary koinobiont endoparasitoid. The results of this study showed that although the parasitoid was observed to oviposit more than once in a host larva, when parasitized larvae were singly isolated in vials, each yielded only one parasitoid cocoon, suggesting the solitary nature of C. icipe .…”
Section: Discussionmentioning
confidence: 99%
“…Solitary (Gao et al., ) and gregarious species (Vos & Vet, ) are found in the genus Cotesia , but C. icipe has consistently proven to be a solitary koinobiont endoparasitoid. The results of this study showed that although the parasitoid was observed to oviposit more than once in a host larva, when parasitized larvae were singly isolated in vials, each yielded only one parasitoid cocoon, suggesting the solitary nature of C. icipe .…”
Section: Discussionmentioning
confidence: 99%
“…Parasitic wasps constitute a major class of natural enemies of many agriculture pests and have tremendous value as biocontrol agents. Most known parasitoid wasp species attack the egg, larval or pupal stages of their hosts and they carry virulence and some other parasitic factors to modify hosts’ physiology and immunity, to change hosts’ metabolism, to destruct hosts’ endocrine and reproductive structures, and finally kill the hosts for their own development 5 – 8 . Many parasitoids are reported to attack various Drosophilidae species, and the majority of them are larval parasitoids, such as Leptopilina heterotoma , L. boulardi and Asobara tabida 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Parasitoids have evolved immunosuppressive factors, such as polydnaviruses, venom components, and/or teratocyte, that reduce expression of the host CTL genes. These endoparasitoid factors manipulate many aspects of their hosts in ways that favor parasitoid development (Fang et al., ; Gao et al., ; Wu et al., ).…”
Section: Introductionmentioning
confidence: 99%